2018
DOI: 10.1097/pr9.0000000000000638
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain in leprosy: symptom profile characterization and comparison with neuropathic pain of other etiologies

Abstract: Introduction: Previous studies reported a high prevalence of neuropathic pain in leprosy, being especially present in “pharmacologically cured” patients. The presence of neuropathic pain in leprosy poses a supplementary burden in patient's quality of life, daily activities, and mood. Objectives: The aim of this study was to assess whether neuropathic pain in leprosy has similar symptom profile as neuropathic pain of other etiologies and to retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
14
0
2
Order By: Relevance
“…In leprosy, the frequency of neuropathic pain ranges from 11.3 to 70.3% [ 12 , 17 , 20 , 27 ]. In our Leprosy Outpatient Clinic based in Rio de Janeiro, the annual prevalence is 15% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In leprosy, the frequency of neuropathic pain ranges from 11.3 to 70.3% [ 12 , 17 , 20 , 27 ]. In our Leprosy Outpatient Clinic based in Rio de Janeiro, the annual prevalence is 15% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tibial nerve neuropathy may be underdiagnosed, as tibial neuritis may develop silently [ 41 ]. Chronic pain is defined as persistent or recurrent for more than or equal to 3 months [ 42 ], and it is known that the neuropathic component in chronic pain impacts more on the quality of life [ 10 ] than pain without the neuropathic component [ 43 ]. All individuals with NP presented chronic pain intermittently or continuously and 93% reported moderate to severe pain.…”
Section: Discussionmentioning
confidence: 99%
“…All individuals with NP presented chronic pain intermittently or continuously and 93% reported moderate to severe pain. These findings show the chronic suffering to which patients are submitted and the lack of diagnosis of NP [ 42 ]. Given that the sampling of this study was randomly obtained, it was not possible to compare individuals with neuropathic and nociceptive pain, which is a limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is rarely recognized as a symptom in leprosy, as leprosy is well known to cause loss of sensation, disability, and disfigurement. Neuropathic pain in leprosy is not routinely investigated in population-based studies; however, recent studies have shown that neuropathic pain can develop several years after the completion of leprosy chemotherapy [45] and the prevalence of pain ranges from 11 to 66%, probably due to differences in study design and clinical setting [45][46][47].…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Neuropathic pain in leprosy may respond to drugs usually used to control pain of neuropathic origin in general. Amitriptyline may be a potential candidate to be tested in clinical drug trials aimed at controlling neuropathic pain in leprosy [46].…”
Section: Neuropathic Painmentioning
confidence: 99%